Enhancing productivity, profitability and quality of garlic (Allium sativum L.) through soil and foliar application of FeSO4 in arid regions - Ronak Kuri; Santosh Choudhary; S.K. Moond; P.R. Raiger; Suman Poonia (Annals of Agricultural Research, 2024)
A field experiment was conducted during the Rabi 2021-22 at College of Agriculture, Jodhpur, involving seven treatments viz., three soil applications of FeSO4 (5, 10, and 15 kg/ha), three foliar applications of FeSO4 (0.3%, 0.5%, and 0.7%), and a control. The experiment was laid out in a Randomized Block Design with three replications. Results indicated significant improvements in growth parameters, bulb attributes, and yield with FeSO4 treatments. The foliar application of FeSO4 at 0.7% recorded highest plant height (69.5 cm) and bulb yield (14.6 t/ha), representing a 26.96% increase over the control. Quality parameters such as TSS content and Fe content in bulbs were also significantly enhanced, with the highest values observed in the foliar application of FeSO4 0.7%. Economic analysis revealed that foliar application of FeSO4 0.7% provided highest net returns (`432,621/ha) and B:C ratio (2.84), followed by soil application of FeSO4 at 15 kg/ha with net returns of `416,961/ha and a B:C ratio of 2.76. Foliar application method demonstrated higher Fe use efficiency compared to soil applications. These findings suggest that foliar application of FeSO4 can be a practical and economically viable strategy for improving garlic production in Fe-deficient soils.